2019
DOI: 10.1146/annurev-marine-010318-095114
|View full text |Cite
|
Sign up to set email alerts
|

Marine Environmental Epigenetics

Abstract: Marine organisms' persistence hinges on the capacity for acclimatization and adaptation to the myriad of interacting environmental stressors associated with global climate change. In this context, epigenetics-mechanisms that facilitate phenotypic variation through genotype-environment interactions-are of great interest ecologically and evolutionarily. Our comprehensive review of marine environmental epigenetics guides our recommendations of four key areas for future research: the dynamics of wash-in and wash-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
187
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(194 citation statements)
references
References 200 publications
(203 reference statements)
7
187
0
Order By: Relevance
“…A recent study in Platygyra daedalea for the first time demonstrated intergenerational inheritance of DNA methylation patterns in corals, from parent to sperm, and evidence for maternal and paternal effects in larvae from reciprocal crosses (Liew, Howells, et al, ). In most animals with early germline segregation, epigenetic marks are reset during meiosis, and the mechanisms of inheritance of epigenetic marks in coral embryos are unknown (reviewed by Eirin‐Lopez & Putnam, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Platygyra daedalea for the first time demonstrated intergenerational inheritance of DNA methylation patterns in corals, from parent to sperm, and evidence for maternal and paternal effects in larvae from reciprocal crosses (Liew, Howells, et al, ). In most animals with early germline segregation, epigenetic marks are reset during meiosis, and the mechanisms of inheritance of epigenetic marks in coral embryos are unknown (reviewed by Eirin‐Lopez & Putnam, ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the different epigenetic mechanisms known to date, DNA methylation is the best studied in marine organisms (Beal et al, ; Eirin‐Lopez, & Putnam, ). In the present work, the analysis of global DNA methylation did not detect significant differences among different nutrient treatments or across different time points (Figure b).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the canceling effect that specific local modifications may have on each other cannot be neglected. Lastly, both promoter and gene‐body methylation (or the lack thereof) appear to contribute to phenotypic plasticity in marine invertebrates (Eirin‐Lopez, & Putnam, ; Gavery & Roberts, ; Li et al, ; Marsh & Pasqualone, ), making the study of this epigenetic mechanism extremely complex in this group. An illustration of such complexity is exemplified by responses to stress involving an increase in DNA methylation at specific genomic regions accompanied by demethylation at others, resulting in a net genome‐wide DNA methylation level similar to that present in controls (same number of DNA methylation marks but at different genomic regions).…”
Section: Discussionmentioning
confidence: 99%
“…Transgenerational acclimatization can be adaptive if the conditions (such as thermal stress) experience by one generation lead to improved performance under those same conditions in the following generation (Torda et al, ), so this pathway is a potentially rapid and important mechanism by which corals may improve their capacity to deal with climate change. At present, the framework for understanding these impacts is complicated by the life‐history and symbiotic nature of corals (reviewed by Eirin‐Lopez & Putnam, ), but epigenetic changes or transgenerational acclimatization is an important area of research that should answer questions about changes in methylation, the downstream influence of these changes on gene expression and if these changes are adaptive.…”
Section: Ecological Signatures Of Acclimatization In Coralsmentioning
confidence: 99%